Quantum Key Distribution Using BB84 Protocol: A Computational Study of Error Rates - Pokharel, Abhinav; Dangol, Rupisha; Neupane, Hari K. (Journal of Nepal Physical Society, 2025)
Quantum key distribution (QKD) enables secure communication using the principles of quantum physics. The BB84 protocol is not only effective for secure key sharing but also for detecting eavesdropping. This study simulates a computational model of QKD and analyzes error rates under varying numbers of bits. Using Python-based simulations with n = 10, n = 100, and n = 1000 bits, and a fixed noise probability of 0.02, we evaluated scenarios both with and without eavesdropping over 1000 trials. The results show an average error rate of 2% without eavesdropping and over 26% with eavesdropping. Standard deviation increases with lower n, indicating higher variability. This study validates BB84’s robustness under noise and demonstrates its sensitivity to third-party interference.